2011
DOI: 10.5588/ijtld.10.0553
|View full text |Cite
|
Sign up to set email alerts
|

Different therapeutic responses in chronic obstructive pulmonary disease subgroups

Abstract: S E T T I N G : Eleven referring hospitals in South Korea. O B J E C T I V E :To compare therapeutic responses in chronic obstructive pulmonary disease (COPD) subgroups, classifi ed by diffusing capacity of the lung for carbon monoxide (DL CO ) and lung volume. D E S I G N : A total of 130 stable male COPD patients were classifi ed into four subgroups according to baseline DL CO and residual volume/total lung capacity (RV/TLC) ratio. We compared therapeutic responses to short acting β 2 -agonist (SABA) and 3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The interim analyses of the KOLD Cohort Study identified various predictors of therapeutic response8,9,10,11. These include clinical, pulmonary functional, radiological or combined factors.…”
Section: Resultsmentioning
confidence: 99%
“…The interim analyses of the KOLD Cohort Study identified various predictors of therapeutic response8,9,10,11. These include clinical, pulmonary functional, radiological or combined factors.…”
Section: Resultsmentioning
confidence: 99%
“… 26 In the Korean Obstructive Lung Disease (KOLD) cohort, chronic bronchitis was present in about 15% of COPD patients, 27 and the difference in clinical phenotype was found to possibly affect the response to pharmacological treatment. 28 29 30 31 Previous clinical trials in patients with severe or very severe COPD show that roflumilast reduces the frequency of exacerbations in a subset of COPD patients with chronic bronchitis. 11 Regrettably, our study did not have sufficient power to evaluate the effects of treatment on the frequency of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to apply therapeutic strategies that are similarly effective for all patients. According to recent reports, COPD patients were classified into their categories based on their response to the specific bronchodilators; however they could not find the relation between the categories and clinical outcome ( 4 , 12 , 13 , 15 ). For example, Albert et al ( 12 ) evaluated BDR as a potential COPD phenotype and indicator of therapeutic response, but found that BDR was not related to any particular clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies support the effectiveness of bronchodilator and anti-inflammation therapy to improve lung function in specific subgroups of COPD patients ( 1 , 4 ). Several studies have found a significant relationship between the decline in lung function and poor clinical outcomes in COPD patients ( 5 , 6 , 7 , 8 , 9 ), but few have shown that improved lung function translates into improved clinical outcomes, including decreased exacerbation ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 96%